Scientific Literacy in Science Lesson - Utami, Budi; Saputro, Sulistyo; *, Ashadi; Masykuri, Mohammad (Sebelas Maret University, 2016)
The aim of this study was to determine: 1) definition of scientific literacy, 2) aspects of scientific literacy. 3) Kinds of scientific literacy, 4) the role of curriculum in 2013 to develop scientific literacy. The method of this paper is research note paper, with a literature review of research journals about scientific literacy in science learning. Â The Curriculum 2013 has emphasized scientific literacy on the learning process by suggesting the utilize of the scientific approach. The scientific approach provides an opportunity for students to perform contextual learning, therefore the learning experiences that students got becomes more meaningful. The scientific approach provides an opportunity for students to connect between the previous concept, the concept being studied and its relationship with other materials that are expected able to improve the scientific literacy of students. The scientific approach to learning science developed from the scientific method commonly known as the science process skills.